Policy uncertainty, financial stability, and stress testing - Paul H. Kupiec (American Enterprise Institute (AEI), 2019)
Since the 2009 Supervisory Capital Assessment Program (SCAP), US regulators have employed a representative bank model as the benchmark of comparison in mandatory stress test exercises. For risk management functions, a bank's own stress model must be calibrated to reflect the bank's historical performance. I analyze stress test forecasts produced by individual bank and a representative bank stress test models. Each model is calibrated using different data, but an identical statistical approach similar to the Fed's 2009 SCAP CLASS model. I compare stress test forecasts to actual institution performance over the first 3 years of the financial crisis. Forecasts from the representative bank model differ dramatically from those produced by bank specific models and actual outcomes. The results highlight the policy uncertainty inherent in using stress tests, both to set minimum bank capital requirements and to assess the capital adequacy needed to maintain banking system stability.
Keywords: A; 330; financial stability; banking